Surface Roughness and Translucency of Various Translucent Zirconia Ceramics after Hydrothermal Aging - Peampring, Chaimongkon; Kengtanyakich, Santiphab (European Journal of Dentistry, 2021)
Objective This study investigated the effect of hydrothermal aging on surface roughness and translucency of various translucent zirconia materials.Materials and Methods Four types of zirconia were tested. Group 1 was translucent zirconia with no cubic structure. Group 2, 3, and 4 included cubic-containing zirconia with different amounts of cubic structures (less than 30%, 30–50%, and more than 50%, respectively). Each group contained 15 disk-shape specimens with dimensions of 15 mm in diameter and 1 mm in thickness. As-sintered surface roughness, translucency parameter, and contrast ratio were evaluated in the two different sessions, before and after aging.Statistical Analysis Two-way repeated measures ANOVA with Bonferroni test was used to analyze statistically significant difference in those tested parameters. Phase structure before and after aging was analyzed by X-ray diffraction analysis (XRD).Results Groups 1 and 2 showed significant increased surface roughness after aging while groups 3 and 4 showed no alteration of surface. There was no effect of aging on translucency in all groups. After aging, group 1 and 2 presented monoclinic structure (16.63 and 5.01%, respectively).Conclusion Hydrothermal aging caused phase transformation and increasing surface roughness in group 1 and 2 but did not affect translucency in all groups.
Keywords: zirconia; hydrothermal aging; surface roughness; translucency parameter; contrast ratio